Effect of Guided Inquiry-Based Laboratories on Improving Students’ Performance in Chemistry Education - Daniel Hanyurwumutima; Emmanuel Gakuba; Wellars Utetiwabo (Journal of Research in Education and Pedagogy, 2026)
This study undertook an investigation of the pedagogical efficacy of guided inquiry-based laboratory activities on improving students’ performance in chemistry education across four secondary schools in Rwanda. The investigation was necessitated by a persistent decline in learners’ achievement in Organic Chemistry, unfavorable learner attitudes, minimal hands-on engagement, and entrenched reliance on experimental verification rather than inquiry-driven exploration during practical sessions. The study further sought the teachers’ perceptions of guided inquiry-based laboratory activities, identified the challenges constraining their implementation, and determined their influence on students’ academic outcomes. This study used a mixed-methods research design with stratified and purposive sampling to identify four chemistry teachers and 447 students, with an 82-sample size from senior five students studying chemistry at the advanced level. The study employed a one-group, pretest-posttest design with experimental and control groups. Data were gathered utilizing a practical lesson observation schedule, a teacher-structured interview, and a student questionnaire. The findings revealed that inadequate laboratory facilities and insufficient teacher professional development perpetuated the dominance of demonstration-based instructional strategies. Moreover, the examination-oriented national curriculum framework implicitly prioritized theoretical mastery and procedural replication over inquiry-oriented laboratory engagement. Notwithstanding these constraints, guided inquiry-based laboratory activities were found to substantially enhance students’ conceptual understanding, cognitive engagement, and attitudinal disposition toward Organic Chemistry. The control group’s mean score improved from 23.5 to 28.7; the experimental group demonstrated a more pronounced gain, increasing from 24.08 to 33.5, accompanied by reduced posttest score dispersion, indicative of more consistent learning progress. The study concludes that guided inquiry-based laboratory activities possess considerable pedagogical potential in improving Organic Chemistry learning outcomes. It therefore advocates for targeted teacher training initiatives and enhanced resource allocation to facilitate a paradigm shift from demonstration-oriented practices toward inquiry-centered laboratory instruction.